Exploring the Therapeutic Potential of Nutraceuticals in the Management of Diabetes Mellitus: Review Article (Journal of Pharma Insights and Research, 2024)
Diabetes mellitus, a chronic metabolic disorder characterized by hyperglycemia, has become a global health concern due to its increasing prevalence and associated complications. Conventional pharmacological treatments, while effective, often come with adverse effects, prompting a growing interest in exploring natural alternatives, such as nutraceuticals. Nutraceuticals are bioactive compounds derived from food sources that offer potential health benefits beyond basic nutrition. This review article aims to provide a comprehensive overview of the therapeutic potential of nutraceuticals in the management of diabetes mellitus. The article delves into the classification of nutraceuticals, including functional foods, carotenoids, dietary fibers, fatty acids, phytochemicals, herbs, probiotics, and dietary supplements. It highlights the anti-diabetic properties of various nutraceuticals, such as Momordica charantia (bitter gourd), Cinnamomum zeylanicum (cinnamon), Ocimum sanctum (tulsi), and fenugreek, exploring their mechanisms of action and potential therapeutic effects. Furthermore, the review discusses the role of essential micronutrients, including vitamins (C, D, E), minerals (zinc, vanadium), and other bioactive compounds (alpha-lipoic acid, coenzyme Q10, carnitine, inositol) in the management of diabetes. Their potential benefits, mechanisms of action, and recommended dosages are critically evaluated. Overall, this review article provides a comprehensive overview of the therapeutic potential of nutraceuticals in the management of diabetes mellitus, offering insights into their mechanisms of action, efficacy, and potential applications as complementary or alternative therapies